A novel rod-like MnO2@Fe loading on graphene giving excellent electromagnetic absorption properties1. Issue 19 (21st May 2015) - Lv, Hualiang; Ji, Guangbin; Liang, XiaoHui; Zhang, Haiqian; Du, Youwei
<x xml:space="preserve">Abstract</x> The rod-like structure of MnO2@Fe is apt to convert the electromagnetic wave to microcurrent and then attenuate it.